Legal Framework and Employee Liability in Banking Compliance and Crime Prevention: The Case Analysis of Indonesia - Prawitra Thalib; Faizal Kurniawan; Syauqina Maghfirah Salsabila; Mohamad Nur Kholiq (Yustisia, 2025)
These banking crimes, such as fictitious credit, are a significant issue in the banking sector. These crimes involve fraud, such as collusion between bank personnel and affected consumers, leading to losses for banks, clients, the public, and the government. This study provides a comprehensive analysis of the legal implications of employee misconduct in banking, particularly in non-performing loans, focusing on prudential banking principles and statutory regulations. This study used a legal research method with a statutory, conceptual, and case approach. The study reveals the role of bank employees in ensuring bank compliance and preventing banking crimes. It highlights the responsibilities of Credit Decision Makers, Credit Analysts/Marketing, and Credit Administration in ensuring compliance with prudential principles. The author suggests that violations of Article 49 paragraph (2) letter a in Indonesia Banking Law should be classified as banking crimes rather than corruption crimes. A proactive approach from all banking elements, including internal audits and government support, is needed to prevent such crimes. The study also concludes that the legal liabilities of bank employees in non-performing loan cases primarily stem from breaches of prudential principles